UMPSA lecturer’s innovation simplifies farm and aquaculture automation through SELESAI Board, wins gold at ITEX 2025 - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 10 July 2025 – A high-impact research initiative from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) bore fruit when a smart automation technology innovation based on the Internet of Things (IoT), known as the SELESAI Board, won a gold medal at ITEX 2025.